PENGARUH PENDIRIAN PERUSAHAAN PERTAMBANGAN EMAS KOLONIAL BELANDA DI LEBONG TAHUN 1897-1930 - Siti Rahmana (JURNAL AGHNIYA, 2018)
Lebong was a region that included in the Regency of Bengkulu. In 1897 to 1930, Lebong be one of the areas in the Netherlands East Indies  the productive yield minerals in the form of gold. There are three privately-owned gold mining company Netherlands and two gold mining company owned by the Government of Netherlands East Indies. This research was carried out with the use of historical methods of heuristics, critique of sources, interpretations and historiography. The results obtained from the study shows that there is a significant change for the Lebong, both from the governmental system, city planning, as well as the composition of the society. These changes occurred after the establishment of the colonial Netherlands Gold Mining Corporation. The local government system is limited and got control of regulations enacted by the Government of Netherlands East Indies. In addition, the presence of a gold mining company Colonial Netherlands made of roads, thus facilitating mobility in the Lebong. Netherlands Indies Government built facilities such as offices, factories, residences, places of entertainment, and means of education to support sustainability of gold mining companies. On the other hand, the existence of the colonization program drawn from Java to the region to meet the needs of kuli of contracts for mining companies make Lebong bustling city as population and economic activity will be.Keywords : significant, mobility, colonization